Functional anatomy of a giant toothless mandible from a bird-like dinosaur: Gigantoraptor and the evolution of the oviraptorosaurian jaw. Issue 1 (December 2017) - Ma, Waisum; Wang, Junyou; Pittman, Michael; Tan, Qingwei; Tan, Lin; Guo, Bin; Xu, Xing
Abstract The Oviraptorosauria are a group of theropod dinosaurs that diverged from the typical carnivorous theropod diet. It includes two main lineages – Caenagnathidae and Oviraptoridae – that display a number of differences in mandibular morphology, but little is known about their functional consequences, hampering our understanding of oviraptorosaurian dietary evolution. This study presents the first in-depth description of the giant toothless mandible ofGigantoraptor, the only well-preserved stemward caenagnathid mandible. This mandible shows the greatest relative beak depth among caenagnathids, which is an adaptation seen in some modern birds for processing harder seeds. The presence of a lingual triturating shelf in caenagnathids more crownward thanGigantoraptor suggests a possible increased specialization towards shearing along this lineage. Like other oviraptorosaurs, the possession of a dorsally convex articular glenoid inGigantoraptor indicates that propalinal jaw movement was probably an important mechanism for food processing, as inSphenodon and dicynodonts. Oviraptorid mandibles were more suited for producing powerful bites (e.g. crushing-related) compared to caenagnathids: oviraptorids generally possess a deeper, more downturned beak, a taller coronoid process prominence and a larger medial mandibular fossa. This disparity in caenagnathid and oviraptorid mandible morphology potentially suggests specialization towards two different feeding styles – shearing and crushing-related mechanisms respectively.